Production and development of vaccines for ornithobacterium rhinotracheale infection in turkeys - Osman Erganis; Hasan Hüseyin Hadimli; Kursat Kav; Zafer Sayin; Zeki Aras (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study was to prepare bivalent inactive Ornithobacterium rhinotracheale bacterin vaccines to measure the levels of antibodies against antigens in blood sera and to determine the efficacies of different O. rhinotracheale vaccines on turkeys. Materials and Methods: The bivalent inactivated O. rhinotracheale bacterin vaccines were prepared from O. rhinotracheale serotype A and B strains using aliminium hydroxide, mineral oil, aluminium hydroxide + ginseng and mineral oil + ginseng. After the sterility and the safety tests, laboratory efficiencies of vaccines (challange/protection and serological potency) were done on the turkeys (twice vaccinated with doses 0.25 ml and 0.5 ml at 5 and 8 weeks, respectively). Results: According to the challenge results, all the vaccines were found effective at 100%. Slide agglutination, micro serum agglutination and ELISA tests were used for the diagnosis. The vaccine containing mineral oil and ginseng as adjuvant induced significantly greater humoral immune response than others. Also, vaccine containing mineral oil and ginseng as adjuvant was determined to be more effective in the field trials in a company privately producing turkeys. Conclusion: O. rhinotracheale vaccines could be used for prevention of ornithobacteriosis in turkeys.